Analysis of the Effect of Return on Equity and Earning Per Share on the Share Price of PT Kalbe Farma, Tbk with the Rupiah Exchange Rate as a Moderating Variable - Siagian, Bangun Batahan; Samosir, Partogi Saoloan (Journal of Islamic Studies & Social Science, 2025)
This study aims to analyze the effect of fundamental company factors, namely Return on Equity (ROE) and Earning Per Share (EPS), on Stock Prices with the Rupiah Exchange Rate as a moderating variable. The research focuses on the pharmaceutical and banking industries, specifically PT Bank Mandiri (Persero), Tbk and PT Kalbe Farma, Tbk, during a 42-month period from January 2016 to June 2019. The method used is quantitative research with associative analysis to test the causal relationship between variables. Data analysis techniques included classical assumption testing, multiple linear regression, and Moderated Regression Analysis (MRA) to determine whether the Rupiah Exchange Rate strengthens or weakens the relationship between independent variables and stock prices. This study is expected to provide investors with an overview of financial performance and the influence of macroeconomic variables before investing in the capital market.